Evaluation of the relapse prevention program for substance abusers called "TAMARPP" at mental health and welfare center - Kondo, Ayumi; Ide, Mihoko; Takahashi, Ikue; Taniai, Tomoko; Miura, Kasumi; Yamaguchi, Akiko; Yotsuji, Naomi; Matsumoto, Toshihiko (Nihon Arukoru Yakubutsu Igakkai zasshi = Japanese journal of alcohol studies & drug dependence, 2014)
We developed the TAMA mental health and welfare center Relapse Prevention Program (TAMARPP) and evaluated the efficacy of the program. We provided the program for 59 substance abusers at Tokyo Tama Comprehensive Mental Health and Welfare Center, and conducted brief interviews and questionnaire surveys to them four times during eight months follow-up period. The main results were as follows. 1) Most of the subjects were before "hitting bottom". 2) More than half of the subjects continued participating in the program for more than 2 months and their attendance rate was fairly high. 3) Some of the subjects began joining a self-help group as N.A. and A.A. during the follow up period. 4) The mood states of the subjects were gradually improved during the period. 5) About one-third of the subjects abused substance again after two-month' program, but all of them continued to attend the program or a private counseling. Most of their families also continued having support from the center. These findings suggested it was meaningful to have such a friendly and less confrontational program as TAMARPP at our center to provide support for many substance abusers before "hitting bottom" and their families.